Price, location, and physical evidence against decision of budget traveler stay at Oyo Rajawali Homestay Palembang - Tampubolon, Maranatha Stephanie; Wahab, Zakaria; Isnurhadi, H.; Sulastri, Hj. (International research journal of management, IT and social sciences, 2020)
Tourism is closely related to the service and hospitality business. The hospitality business began to shift towards technology in 2015. This led to the emergence of various Virtual Hotel Operators, such as OYO. One of OYO’s budget hotels in Palembang which is famous for its strategic location, affordable prices, and adequate physical evidence is Rajawali Homestay. This study aims to determine whether the price, location, and physical evidence affect the budget traveler’s decision to stay at the hotel. The data used in this study are primary data by distributing questionnaires to all budget travelers who stay at OYO Rajawali Homestay. The number of samples used was 100 respondents. The analysis technique used is multiple linear regression analysis that was previously tested for validity and reliability. The results obtained are the price, location and physical evidence have a positive and significant impact on budget traveler’s decision to stay at OYO Rajawali Homestay. The percentage of influence between the three variables on purchasing decisions is 77% of which 33% is influenced by other variables not examined. This research is expected to be a reference to optimize the variables that influence budget travelers’ decisions in choosing hotels.